2013
DOI: 10.1371/journal.pone.0064930
|View full text |Cite
|
Sign up to set email alerts
|

IKKε Knockout Prevents High Fat Diet Induced Arterial Atherosclerosis and NF-κB Signaling in Mice

Abstract: AimsAtherosclerosis is a public health concern affecting many worldwide, but its pathogenesis remains unclear. In this study we investigated the role of IKKε during the formation of atherosclerosis and its molecular mechanism in the mouse aortic vessel wall.Methods and ResultsC57BL/6 wild-type or IKKε knockout mice bred into the ApoE knockout genetic background were divided into 4 groups: (1) wild-type (WT), (2) ApoE knockout (AK), (3) IKKε knockout (IK), (4) or both ApoE and IKKε knockout (DK). Each group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…As discussed above, it seems that multiple mechanisms are involved, but one of the first and potentially most important control mechanisms characterized for inflammation is its regulation of weight gain. The most significant metabolic effect of IKKε knockout in our study was also the prevention of weight gain on a HFD, which is consistent with recent advancements in the development of atherosclerosis from our laboratory (21). Thus, limitations of this study include the influence of the prevention of weight gain on inflammation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As discussed above, it seems that multiple mechanisms are involved, but one of the first and potentially most important control mechanisms characterized for inflammation is its regulation of weight gain. The most significant metabolic effect of IKKε knockout in our study was also the prevention of weight gain on a HFD, which is consistent with recent advancements in the development of atherosclerosis from our laboratory (21). Thus, limitations of this study include the influence of the prevention of weight gain on inflammation.…”
Section: Discussionsupporting
confidence: 80%
“…ApoE knockout [ApoE(/)] mice were obtained from the Model Animal Research Center of Nanjing University at the age of 8 weeks. IKKε knockout mice were bred into the ApoE knockout genetic background to obtain the ApoE(-/-)/IKKε(-/-) group of mice, as reported previously (21). At the age of 8 weeks, the male ApoE(-/-) and ApoE(-/-)/IKKε(-/-) mice were placed on a HFD containing 60% calories of lipid (soybean oil, 5.5%; lard, 54.5%; D12492; Research Diets, Inc., New Brunswick, NJ, USA) and fed for 12 weeks, whereas the remaining mice were kept as controls on a standard ND containing 10% calories for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The role of IKKe in the development of atherosclerosis was further verified in our previous investigation, and recent studies have confirmed that atherosclerosis is a risk factor for AA [1,6,13]. Matrix metalloproteinase-2 (MMP-2), a downstream of IKKe, is widespread and responsible for extracellular collagen degradation and remodelling [8].…”
Section: Introductionsupporting
confidence: 65%
“…The next day, after washing with TBST four times for 10 min each time at room temperature, the PVDF membranes were incubated with proportionally diluted peroxidase-conjugated goat anti-rabbit secondary antibodies (1:1000; Beijing ZhongShan Biotechnology Co.) for 1 h. Furthermore, for the specific proteins, we used an ECL reagent (GE Healthcare, Piscataway, NJ, USA) to detect and capture images on Hyperfilm (Amersham, GE Healthcare). Ultimately, we evaluated the results using Image J software [1] for semi-quantitation of the mean grey value of each blot. All the details of antibodies are in additional information Table 2.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…An NF-κB decoy oligonucleotide inhibited neointima formation in rats [27]. The knockdown of IKKε decreased atherosclerosis [28], as did a cell-permeable peptide that inhibited the nuclear import of NF-κB [29], the NF-κB inhibitor dehydroxymethylepoxyquinomicin [30] and the endothelial-specific inhibition of NF-κB [31] in mice. Haemopoietic deficiency of the gene encoding for p50 led to smaller, but more inflammatory, lesions in mice [32].…”
Section: Introductionmentioning
confidence: 99%